Vasoneuronal coupling in migraineurs after subcutaneous sumatriptan: a TCD study - Bäzner, Hansjörg; Steinke, Wolfgang; Daffertshofer, Michael; Hennerici, Michael G. (Journal of the neurological sciences, 1999)
According to the trigeminovascular model of pain in migraine, sterile neurogenic inflammation of dural vessels stimulates nociceptive fibres of the trigeminal nerve. Sumatriptan, a 5-HT1 receptor agonist, blocks this reaction and mediates vasoconstriction of meningeal arteries. However, it is uncertain, whether sumatriptan also has a vasoconstrictive effect on cerebral arteries, which may influence vasoneuronal coupling and induce secondary cerebral blood flow changes. We studied changes of cerebral blood flow velocity (CBFV) and the pulsatility index (PI) in the posterior cerebral artery (PCA) after stimulus activation before, 10 min and 30 min after subcutaneous application of 6 mg sumatriptan, in order to assess potential vasoactive effects on cerebral circulation. CBFV was recorded from both PCAs simultaneously in 27 migraineurs (twenty women, seven men, mean age 29 years), and arterial blood pressure (BP), heart rate (HR) and respiration rate (RR) were monitored. Although the mean diastolic blood pressure rose significantly from 75 mm Hg to 81 mm Hg (P<0.05) and systolic blood pressure and respiration rates remained constant, average CBFV values remained constant. Similarly, the relative increase of CBFV by visual stimulation, which is clearly higher compared to controls in other studies (55.0% before, 52.6% after 10 min, and 52.4% after 30 min), and absolute mean values for CBFV and PI did not change after visual stimulation. These results provide evidence against the hypothesis that sumatriptan produces vasoconstriction in the intracranial human arterial circulation as a potential risk of cerebral ischemia.
Gesehen am 28.07.2022